Antiviral Activity of Rambutan Peel Polyphenols Obtained Using Green Extraction Technology and Solvents - Christian Hernández-Hernández; Luis E. Estrada-Gil; Sonia A. Lozano-Sepúlveda; Ana M. Rivas-Estilla; Mayela Govea-Salas; Jesús Morlett-Chávez; Cristóbal N. Aguilar; Juan A. Ascacio-Valdés (Sustainable Chemistry)
Rambutan peel is a great source of bioactive compounds, the same that, over the years, has been extracted using conventional technologies which have been proven to be harmful to the environment and potentially toxic to human beings. This study aimed to extract the same compounds using a hybridization of ultrasound/microwave extraction. The results were promising, as a total of 378.48 ± 9.19 mg/g of polyphenols were recovered from this procedure, and the most important molecules (geraniin, corilagin, and ellagic acid) were identified, giving this much more relevance. Furthermore, treatment with rambutan peel extract recovered with green technologies significantly reduced cell viability in HCV-infected liver cells. Notably, higher concentrations (4000 and 5000 ppm) led to more pronounced cell death in huh7 cells. The treatment also led to a significant reduction in viral protein and RNA expression in HCV-infected cells. These findings suggest that rambutan peel extract obtained from the combination of ultrasound and microwave extraction, particularly the ellagitannins present, have potential antiviral properties. Further research is needed to explore its mechanism of action and its potential as a therapeutic agent for Hepatitis C.